Dietary Antioxidants and FEV(1) Decline: the Health, Aging and Body Composition Study - Bentley, Amy R (2011)
Increased antioxidant defenses are hypothesized to decrease age- and smoking-related decline in lung function. The relation of dietary antioxidants, smoking, and forced expiratory volume in the 1(st) second of effort (FEV(1)) was investigated in community-dwelling older adults in the Health, Aging, and Body Composition Study. 1,443 participants completed a food frequency questionnaire, self-reported smoking history, and had measurements of FEV(1) at both baseline and after 4 years of follow-up. The association of dietary intake of nutrients and foods with antioxidant properties and rate of FEV(1) decline was investigated using hierarchical linear regression models. In continuing smokers (current smokers at both time points), higher vitamin C and higher intake of fruits and vegetables were associated with an 18 and 24 ml/year slower rate of FEV(1) decline compared to lower intake (P<0.0001 and 0.003, respectively). In quitters (current smoker at study baseline, quit during follow-up), higher intake was associated with an attenuated rate of decline for each nutrient studied (p<0.003, all models). In non-smoking participants, there was little or no association of diet and rate of decline in FEV(1). The intake of nutrients with antioxidant properties may modulate lung function decline in older adults exposed to cigarette smoke.